Transport-related airborne nanoparticles: Sources, different aerosol modes, and their toxicity. (15th May 2023) - Vouitsis, Ilias; Portugal, José; Kontses, Anastasios; Karlsson, Hanna L.; Faria, Melissa; Elihn, Karine; Juárez-Facio, Ana Teresa; Amato, Fulvio; Piña, Benjamin; Samaras, Zisis
Abstract: Nanoparticle emissions from transport are of considerable importance because of their dominance in terms of particle number concentration in most urban atmospheres. Nanoparticles may carry toxic substances, posing a serious threat to pedestrians, passengers and residents. The road sector has been studied intensively in both academia and industry and considerable knowledge has already been gathered. Shipping is also a significant source of nanoparticles both at the global and the European level and may be responsible for cardiopulmonary diseases and lung cancer at the global level, while ship emissions are known as one of the least regulated sources of pollutants. Aviation nanoparticle emissions have also received increasing attention in recent years because of the rapid growth of air transport volumes and the expected expansion to meet capacity needs for future years. Exhaust nanoparticle emissions from diesel rail transport are not very well known and only a few sources addressing actual emission rates are available. All modes of transport are sources of non-exhaust nanoparticle number emission associated with the tire, brake, and road/rail surface wear and tear. This paper provides a literature review to identify the different aerosol modes (i.e., primary, delayed primary, and secondary) from each transport source (road, shipping, aviation, rail), in both laboratory and field tests and to explore their toxicity relevance. The review focuses on nanoparticles (<100 nm) and investigates both exhaust and non-exhaust emissions. We present details on nanoparticles produced by transport sources in the urban environment and parameters that influence nanoparticle emissions. Also, we review the potential relationship between the different aerosol modes and their toxicity effects and point out some issues concerning nanoparticle collection for chemical and toxicity characterization. As regards the toxicity part, it is concluded that transport sources emit large number of nanoparticles which may pose a health risk. They can damage the respiratory tract and lungs, thus playing a crucial role in the physiology of pulmonary pathologies. These nanoparticles can also affect other organs, and the cardiovascular, nervous, and reproductive systems. The combination of oxidative stress, mitochondrial damage, inflammation, and activation of apoptosis, are the initiators of the systemic toxicity of nanoparticles, triggered by a unique combination of heavy metals and organic compounds present in combustion products. Highlights: The size of nanoparticles determines (in a probabilistic sense) their fate in the air and their toxicity potential. Regulation has contributed to significant emissions reduction from road trasport. Maritime and airport traffic and diesel rail transport contribute to urban nanoparticle pollution. All sources except maritime emit non-exhaust nanoparticles. The particle extraction method from filters can modify the toxic profiles of the extracts. Toxic profile depends on the extraction method but seems to be critical in the physiology of pulmonary pathologies.